2006
DOI: 10.1080/13548500500155941
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting stress through leisure coping: A prospective health study

Abstract: The purpose of this study was to examine stress-buffer or -counteracting effects of leisure coping, by taking into account several key axes of society (i.e., gender, social class, and age) that are essential to characterize the diverse nature of our society. A 1-year prospective survey of a representative sample (n = 938) from an urban Canadian city was conducted. In the total sample, long-term health protective benefits of leisure coping became evident when stress levels were higher than lower (i.e., support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 4 publications
1
51
0
7
Order By: Relevance
“…Leisure was idiosyncratically defined and when participation in such meaningful activities was no longer possible, a multitude of losses were incurred. Moreover, studies have revealed that leisure activity is linked to stress relief, comfort, and personal fulfilment (Fullagar, 2008;Hutchinson et al, 2008;Iwasaki, 2006Iwasaki, , 2007Iwasaki, , 2008Ormel, Lindenberg, Steverink, & Vonkorff, 1997). Thus, both the leisure literature and the present data demonstrate the impact of lost leisure activities on identity in the context of cancer survivorship.…”
Section: Theme 1: a Sense Of Lossmentioning
confidence: 64%
See 1 more Smart Citation
“…Leisure was idiosyncratically defined and when participation in such meaningful activities was no longer possible, a multitude of losses were incurred. Moreover, studies have revealed that leisure activity is linked to stress relief, comfort, and personal fulfilment (Fullagar, 2008;Hutchinson et al, 2008;Iwasaki, 2006Iwasaki, , 2007Iwasaki, , 2008Ormel, Lindenberg, Steverink, & Vonkorff, 1997). Thus, both the leisure literature and the present data demonstrate the impact of lost leisure activities on identity in the context of cancer survivorship.…”
Section: Theme 1: a Sense Of Lossmentioning
confidence: 64%
“…L eisure time, hobbies, pastimes, and active living are integral components of modern life with a variety of motivations and values such as membership in particular social groups, expressions of creativity, and notions of caring for oneself (Rojek, 2005). Leisure activities promote life balance, personal renewal, resilience, and capacity to proactively cope with stress (Fullagar, 2008;Hutchinson, Bland, & Kleiber, 2008;Iwasaki, 2006Iwasaki, , 2007Iwasaki, , 2008. The literature illustrates that leisure is experienced in a variety of individually defined ways, depending on the subjective meanings and perceptions that people have (Greenwood Parr & Lashua, 2004;Holland, 2009;Kim, 2008;Siegenthaler & Vaughan, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, these results lend broad support to theories proposing why leisure is beneficial; although it should be noted that the purpose of this study was to examine the within-person associations in general and thus was not optimally structured to test each specific theory. For example, some work suggests that leisure improves health because it has stress-reducing benefits [8][9][10]. Leisure is proposed to help reduce individuals' current stress levels, such as by providing a break from stressful events or helping to restore normal routines disrupted by stressors [54], and/or improve the ability to cope with current or future stressful events [55].…”
Section: Discussionmentioning
confidence: 99%
“…We examine a small subsample participating in vigorous physical activity preretirement that change to light physical activity postretirement and the impact this change has on PA and NA. Iwasaki (2006) differentiates between leisure coping beliefs (values associated with the therapeutic value of leisure) and leisure coping strategies (which leisure activities help cope with stress). Zuzanek, Robinson, and Iwasaki (1998) highlighted the stress buffering effects of leisure but concluded that higher perceived levels of physical activity resulted in lower levels of stress only for retirees aged 65 and older.…”
Section: Models Of Activity Engagement and Retirement Adjustmentmentioning
confidence: 99%